What are the current challenges of managing cancer pain and could digital technologies help? - Adam, Rosalind (BMJ Support Palliat Care, 2018)
OBJECTIVES: Pain remains a problem for people with cancer despite effective treatments being available. We aimed to explore current pain management strategies used by patients, caregivers and professionals and to investigate opportunities for digital technologies to enhance cancer pain management. METHODS: A qualitative study comprising semistructured interviews and focus groups. Patients with cancer pain, their caregivers and health professionals from Northeast Scotland were recruited from a purposive sample of general practices. Professionals were recruited from regional networks. RESULTS: Fifty one participants took part in 33 interviews (eight patients alone, six patient/caregiver dyads and 19 professionals) and two focus groups (12 professionals). Living with cancer was hard work for patients and caregivers and comparable to a ‘full-time job’. Patients had personal goals which involved controlling pain intensity and balancing this with analgesic use, side effects, overall symptom burden and social/physical activities. Digital technologies were embraced by most patients, and made living life with advanced cancer easier and richer (eg, video calls with family). Technology was underutilised for pain and symptom management. There were suggestions that technology could support self-monitoring and communicating problems to professionals, but patients and professionals were concerned about technological monitoring adding to the work of managing illness. CONCLUSIONS: Cancer pain management takes place in the context of multiple, sometimes competing personal goals. It is possible that technology could be used to help patients share individual symptom experiences and goals, thus enhancing tailored care. The challenge is for digital solutions to add value without adding undue burden.